ANALISIS NUMERIK PENGGUNAAN GEOTEKSTIL DI LAPISAN TANAH DASAR PADA PROYEK PEMBANGUNAN JALAN PONCOSARI-GREGES (KABUPATEN BANTUL, PROPINSI D.I. YOGYAKARTA) - Zainul Faizien Haza (Universitas Sarjanawiyata Tamansiswa, 2017)
Geotextile is normally used in geotechnical and other civil engineering work. Geotextiles have been increasingly applied as reinforcement in road embankments. The purpose of this study is to develop the back calculation on safety factor of the use of geotextile as the reinforcement in road embankment considering the displacement in the Proyek Pembangunan Jalan Poncosari-Greges Kabupaten Bantul, D.I. Yogyakarta. The numerical analysis of the road embankment stability was analyzed by finite element method using PLAXIS. Plane strain model was used in this study to calculate the displacement of the road embankment. Analysis results showed that the safety factor obtained by analysis using PLAXIS on the embankment reinforced geotextile was 1.53, which was greater than the standard of safety factor of 1,2. This study concluded that the road embankment was a safe soil construction for the Project of Jalan Pocosari-Greges Yogyakarta.